A tale of two generations: Case study of intergenerational living in residential aged care. Issue 6 (December 2022) - Gurung, Apil; Edwards, Sam; Romeo, Michele; Craswell, Alison
Abstract: Background: Social isolation and loneliness are associated with major adverse health outcomes and increased mortality. Intergenerational programs provide an opportunity to consider quality interactions that may reduce social isolation and loneliness, supporting older people to build strong and meaningful relationships. Minimal research has been conducted in the Australian context pertaining to intergenerational living involving university students. Aims: To explore an intergenerational residential model of university students residing with older people in a residential aged care facility and examine the impact on social isolation and engagement. Method: Using a case study design, this study explored the experience of a university student, Residential Aged Care Facility (RACF) residents and staff who participated in an intergenerational living trial at a regional Aged Care facility in Queensland, Australia. Findings: Participants indicated that the experience was positive and found the relationships meaningful. For frail older adults the trial provided companionship and reduced isolation. The student gained a deeper understanding of and respect for the older generation; with staff observing an improvement in social interactions between the two. Discussion: The student was noted to be a catalyst for a cultural shift which resulted into more social interactions among residents in the RACF. The intergenerational program was seen as an opportunity for personal growth for the student, with confidence and independence being one the key areas for development. Conclusion: The study reveals that intergenerational living has the potential to be a positive influence on residents, staff, and students, and should be trialled beyond the setting.